Co-ocurrence patterns and feeding behaviour at local scale of Phlebotominae(Diptera: Psychodidae) from Falcon state, Venezuela - Cazorla, Dalmiro J. (2014)
The phlebotomine sandfly are vectors of protozoan parasites Leishmania genus, the causative agents of leishmaniasis in humans and several mammalian hosts. The structure of the phlebotomine sandfly community at the local scale: domicile, peridomicile and sylvatic habitats from a reduced area, was assessed using null models analysis in endemic foci of leishmaniasis from Falcon state, in north-western region of Venezuela. Implementation of null model tests revealed that to a local scale the phlebotomine sandfly communities are aggregated, suggesting that the species co-occurred and did not compete. The assays of co-ocurrence patterns with guild structure analysis and favored states hypothesis showed statistically non-significant results (p> 0.05), suggesting that sandfly species belong to a same guild in relation to their feeding preferences, as hematophagy appears to be an heterogeneous, circumstantial and opportunist event. We discussed aspects of the possible factors, for example sinantropic effects on environmental transformation and its homogenization, that could be determining the phlebotomine sanfly assemblage in the Falcon state region.